Oxidative stability and estimate of the shelf life of sacha inchi (Plukenetia volubilis L.) oil - Rodríguez, Gilbert (2015)
Sacha inchi oil is rich in polyunsaturated fatty acids that may rust, limiting their shel flife. The Rancimat method is official, for evaluations of oxidative stability accelerated in oils. Industrially conventional techniques based on physical and chemical indicators are used; there are no studies of correlation between them and Rancimat. This work has for objective correlate the oxidative stability index (OSI) Sacha inchi oil obtained by Rancimat at temperatures of 80°, 90°, 100° and 110 °C under an air flow of 15 L/h, with the values of physic-chemical indicators such as Index peroxide, p-anisidine, totox and density. Also estimated by mathematical extrapolation, the shelf life of sacha inchi oil to usual storage temperatures. OSI values were: 0.493 ± 0.01 h at 110 ºC, 1.590 ± 0.06 h at 100 ºC, 4.645 ± 0.1 h at 90 ºC and 20.512 ± 0.02 h at 80 ºC. High correlation has been established between values of OSI vs physicochemical quality indices (0.9322 < r < 0.9965). The activation energy was found 137.90 kJ/mol, which explains the high oxidative stability for the oil, estimating a lifetime of 3.29, 1.79 and 0.79 years at 20, 25 and 30 °C respectively.